Personality and Marital Surplus - Shelly Lundberg (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper uses data from the German Socio-economic Panel Study to examine the relationship between psychological traits, in particular personality, and the formation and dissolution of marital and cohabiting partnerships. Changing patterns of selection into and out of relationships indicate that the determinants of marital surplus have altered between older cohorts who were born in the years after World War II and younger cohorts born in the 1960s. For younger cohorts, relationships between personality traits and the probability of marriage are identical for men and women, which is consistent with returns to marriage that are based on joint consumption. Tastes for marital public goods are negatively related to openness to experience (a desire for change and variety) and positively related to conscientiousness for both men and women. Selection into marriage is associated with distinctly different personality profiles for older men and older women, suggesting that gender-specialized contributions to household public goods were an important source of marital surplus for these cohorts.
Keywords: 330; Ehe; Haushaltsproduktion; Persönlichkeitspsychologie; Geschlecht; Scheidung; Lebensgemeinschaft; Schätzung; Deutschland